2018
DOI: 10.17567/ataunidfd.473726
|View full text |Cite
|
Sign up to set email alerts
|

Si̇li̇kon Esasli Yumuşak Astar Materyalleri̇nde Bekletme Süreleri̇ni̇n Sertli̇k Ve Su Emi̇li̇mi̇ Üzeri̇ne Etki̇si̇

Abstract: Aim: The purpose of this research is to investigate the effect of the storage times of silicone-based soft lining material in water on hardness and water absorption of the material. Material and methods: In this study, silicone based soft denture liner Permaflex and isobutylmethacrylateadded form of the same material were used. The soft denture liners were processed according to manufacturers' instructions with the dimension (10x10x1mm) for water sorption tests and (10x10mm) for hardness tests, and then put in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…Generally speaking, all the data's exhibited that the specimens' group that was stored in neutral and alkaline AS for both control and experimental groups recorded the highest mean value; this may be related to the fact that the basic AS contain a large number of hydroxyl ions, which responsible for accelerating the degradation process, thus the surface roughness of the immersed samples is increased, while the specimens' group that was stored in acidic AS for both control and experimental groups recorded the lowest mean value this is may be explained by the losing of some structural ions from acidic saliva made the polymer surface more softness and this findings agreed with [43]who studied the effect of different pH levels of AS on the surface roughness of different materials of acrylic denture base. Also, pervious research evaluated the effect of beverages on surface roughness and hardness of soft lining material and concluded there was significant change in both properties and revealed that the soda group (alkaline group) recorded the highest surface roughness and this was in agreement with the result of current study [2]. While, contradict with previous study who concluded the surface roughness of acrylic resin was increased due to immersion in acidic pH of AS [44].…”
Section: Effect Of Different Ph Levels Of Artificial Saliva On Surfac...supporting
confidence: 72%
See 1 more Smart Citation
“…Generally speaking, all the data's exhibited that the specimens' group that was stored in neutral and alkaline AS for both control and experimental groups recorded the highest mean value; this may be related to the fact that the basic AS contain a large number of hydroxyl ions, which responsible for accelerating the degradation process, thus the surface roughness of the immersed samples is increased, while the specimens' group that was stored in acidic AS for both control and experimental groups recorded the lowest mean value this is may be explained by the losing of some structural ions from acidic saliva made the polymer surface more softness and this findings agreed with [43]who studied the effect of different pH levels of AS on the surface roughness of different materials of acrylic denture base. Also, pervious research evaluated the effect of beverages on surface roughness and hardness of soft lining material and concluded there was significant change in both properties and revealed that the soda group (alkaline group) recorded the highest surface roughness and this was in agreement with the result of current study [2]. While, contradict with previous study who concluded the surface roughness of acrylic resin was increased due to immersion in acidic pH of AS [44].…”
Section: Effect Of Different Ph Levels Of Artificial Saliva On Surfac...supporting
confidence: 72%
“…For more than one century, soft denture lining materials have been utilized in dentistry field [1]. A soft denture lining material also known as a resilient liner, it's a polymeric material, considered as a kind of "shock absorber" between the occluded surfaces of the denture and the underlying oral mucosa to assimilate the mastication forces and distribution it by the means of viscoelastic behavior [2]. There are several conditions needed to use the flexible lining materials for complete dentures like patient has irregularities in the alveolar margin and covered with relatively thin, non-pliable mucosal layer, this is could be painful when chewing forces applied through a solid acrylic bases on this kind of supportive tissue so utilizing soft lining materials will aid in relieving the pain and increasing patient acceptance of dentures [3,4].…”
Section: Introductionmentioning
confidence: 99%